Football supporters` perceptions of their role in the home advantage - Wolfson, S.; Wakelin, D.; Lewis, M. (Journal of Sports Sciences, 2005)
Football fans' views on their role in the home advantage were obtained by placing links to an internet questionnaire on supporters' websites. Altogether, 461 fans from clubs which had been promoted, relegated or unchanged in the past season of the English football leagues rated crowd support as significantly more influential than familiarity, travel, territoriality and referee bias in contributing to the home advantage. Fans felt responsible for inspiring their team to victory, took credit for distracting opponents, and believed that they could influence officials into making decisions in their team's favour. However, they did not accept personal blame for poor results. No effects for gender, age or the team's outcome in the promotion/relegation battle emerged, though season ticket holders were more extreme in their feelings of responsibility overall. Furthermore, it was suggested that mechanisms such as the perception of being superior to rivals can encourage fans to retain their allegiance to their teams, even when outcomes are disappointing. Indeed, affiliation may become so incorporated into self-identity that supporters may not have the option of abandoning their team, but instead perceive a reciprocal relationship in which both they and the team are expected to do their best to achieve success.